AVENIDA ENG. LUIS CARLOS BERRINI: A PRODUÇÃO DO “MODERNO” - Miele, Sávio Augusto de Freitas (GEOUSP Espaço e Tempo (Online), 2006)
At present, São Paulo metropolis is moving from an industrial economy to a modern third economy, which is revealed, by the economic and financial center expansion from downtown of São Paulo in direction to southwest/south area of the city. In this context, we analyse a fragment of São Paulo metropolis, Eng. Luiz Carlos Berrini avenue, which reveals elements for our comprehension of urban space reproduction process in São Paulo and the understanding of the global cities.